2011
DOI: 10.1371/journal.pone.0022111
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Strains of Human Respiratory Syncytial Virus in Central and South America

Abstract: Human respiratory syncytial virus (HRSV) is a major cause of viral lower respiratory tract infections among infants and young children. HRSV strains vary genetically and antigenically and have been classified into two broad subgroups, A and B (HRSV-A and HRSV-B, respectively). To date, little is known about the circulating strains of HRSV in Latin America. We have evaluated the genetic diversity of 96 HRSV strains by sequencing a variable region of the G protein gene of isolates collected from 2007 to 2009 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…In Fortaleza, during the five epidemic periods, genotypes GA2 and GA5 of HRSV‐A occur in varying proportions. Brazilian and international studies have shown a high diversity of genotypes of HRSV with GA2 and GA5 as the predominant circulating genotypes . The small number of strains analyzed should not be the only reason for the low diversity of genotypes of HRSV‐A detected in Fortaleza.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In Fortaleza, during the five epidemic periods, genotypes GA2 and GA5 of HRSV‐A occur in varying proportions. Brazilian and international studies have shown a high diversity of genotypes of HRSV with GA2 and GA5 as the predominant circulating genotypes . The small number of strains analyzed should not be the only reason for the low diversity of genotypes of HRSV‐A detected in Fortaleza.…”
Section: Discussionmentioning
confidence: 93%
“…This genotype, named BA, has a duplication of 60 nucleotides . Since 1999, the BA genotype has spread globally and in some places now predominates or has replaced genotypes that circulated for several years . In Fortaleza, BA strains were detected in 2004 but in 2005, when there was a predominance of HRSV‐A, all five strains of HRSV‐B corresponded to genotype GB3.…”
Section: Discussionmentioning
confidence: 99%
“…GA2 and GA5 circulate worldwide and are recognized as stable genotypes [24], [25], [28], [35][40]. The select dominance of GA2 has also been observed in South Western China during epidemic seasons 2006–2009 [40] and Central and South America [36], Ireland in 2008/2009 [25] and South Africa in 2007–2008 [28]. The efficient circulation of these genotypes could not be explained by high genetic variability of the carboxy-terminal hypervariable region, since this region was remarkably conserved comparing strains isolated over several years [41].…”
Section: Discussionmentioning
confidence: 99%
“…Another Rho family protein, Cdc42 along with WASP and neuronal N-WASP induces Arp2/3-mediated actin branching to form filopodia and granule secretion [343-346]. In the absence of pre-existing actin filaments, IRSp53 initiates this process via its I-BAR domain by bending the membrane outward and binding Cdc42 along with its target proteins.…”
Section: Cdc42-induced Filopodiamentioning
confidence: 99%